Krieg, Verteilungskonflikt, Reparationen: Die deutsche Inflation von 1920 bis 1923 - Albrecht Ritschl (Wirtschaftsdienst, 2023)
– Germany's hyperinflation resulted from a confluence of several factors, all of which contributed to a temporary breakdown in state capacity and to unsustainable public sector deficits. Wartime debt deflated by 90% already in 1920. Informal wage indexation and failure to enforce collection of a new progressive income tax contributed to recurrent inflation. Unsustainable reparations were met by purchasing gold abroad, further accelerating inflation. Conflict over reparation arrears resulted in the military occupation of the Ruhr industry district in early 1923. Stabilisation occurred after informal moratoria on both international and internal conflict, allowing for budget stabilisation and a two-step currency reform, as well as a return to gold in 1924.
Keywords: N14; N4; O10; 330; Hyperinflation; Wirtschaftsgeschichte; Deutschland (bis 1945)